Case-based Learning as a Means of Reforming Pathology Teaching in Second Year Undergraduate Medical Students: An Interventional Study at a Medical College in Maharashtra, India - Vaishali B Nagose; Vipin Narendra Todase; Vilas M Sangole (Journal of Clinical and Diagnostic Research)
Introduction: Case-based Learning (CBL) is a relatively recent Teaching and Learning (TL) method in medical subjects, including pathology, in India. It is learner-oriented, similar to problem-based learning and may enhance medical students’ analytical and problem-solving skills. Aim: To determine the effectiveness of CBL in increasing students’ interest in learning pathology and improving their analytical skills and to assess students’ perception of this method through feedback. Materials and Methods: This comparative interventional study was carried out at Dr. Ulhas Patil Medical College and Hospital, Maharashtra, India over two weeks in August 2020, involving 90 second year undergraduate medical students (II MBBS) studying pathology. The topics were ‘Megaloblastic anaemia’ and ‘Chronic Myeloid Leukaemia (CML)’. Students were divided into two groups (A and B, n=45 each). One group was taught using Didactic Lectures (DL); the other used CBL in small groups. A common Multiple-Choice Question (MCQ) post-test assessed analytical skills after each class. Student feedback on CBL was collected using a five-point Likert scale. Groups were interchanged for the CML session. Mean post-test scores and feedback scores were calculated. Statistical comparison was performed using Student’s t-test (Statistical Package for the Social Sciences (SPSS) version 16.0), with p-value <0.05 considered statistically significant. Results: CBL post-test scores were significantly higher than DL scores (p-value=0.03 and p-value=0.0138). The mean feedback score was excellent (4.4), with most students favouring CBL and reporting superior understanding. Conclusion: CBL promoted active learning, enhancing analytical skills and proving highly acceptable to II MBBS students as a TL method in pathology.